Fibrinolytic Protease-Producing Bacteria with Varied Hemolysis Pattern Associated with Marine Algae Dictyota sp. - Muhammad Ardi Afriansyah; Stalis Norma Ethica (Medical Laboratory Technology Journal, 2023)
The main death factor of cardiovascular disease (CVD) is the formation of a blood clot (thrombus). Thrombus is formed by the action of fibrin, playing a role as a blood coagulation agent. Administration of fibrinolytic enzymes can degrade fibrin through the fibrinolysis process. Therefore, searching for new sources of fibrinolytic enzymes becomes critical in eradicating diseases by fibrinolysis of thrombus. This study aims to isolate fibrinolytic protease-producing bacteria associated with fermented brown algae products Dictyota sp, of Awur Bay, Jepara, Indonesia, and to observe their hemolysis pattern. As many as 14 unique bacterial colonies previously isolated from fermented Dictyota sp. were sub-cultured using Zobell Agar (ZA) medium. Skim Milk Agar (SMA) and Fibrin Agar (FA) were then used as selective media to detect the presence of fibrinolytic protease-producing bacteria, which was indicated by their ability to form a clear proteolytic and fibrinolytic zone simultaneously around bacterial colonies. Hemolysis characteristics of fibrinolytic bacteria were determined using Blood Agar Plate (BAP) to test their ability to produce hemolysin toxin. As a result, of these 14 isolates, 3 of them, namely FD-09, FD-13, and FD-14 (FD= Fermented Dictyota), could produce both proteolytic and fibrinolytic zone with a fibrinolytic index range of 2.0–2.9. Isolate FD-09 is the least pathogenic (g-hemolytic) compared to other fibrinolytic isolates, FD-13 (b-hemolytic) and FD-14 (a-hemolytic), in terms of hemolysin toxicity. In conclusion, fermented Dictyota sp. is a potential source of bacteria-producing fibrin-degrading protease with varied hemolysis patterns. It is necessary to identify bacteria-producing fibrinolytic protease isolates Dictyota sp. and further characterization regarding the specificity and activity of the resulting protease to develop its potential as an antithrombotic agent.